Adventures into the Unknown: A Pilot Interview Study on Business English Teachers' Specialized Competencies and Attributes - Kóris, Rita (Working Papers in Language Pedagogy, 2012)
This paper aims to examine the specialized competencies and attributes that Business English (BE) teachers need in order to run successful BE courses and comply with the requirements of the business community. This small scale qualitative study explores the perceptions of Hungarian BE teachers with extensive BE teaching experience at multinational companies (MNCs) regarding the specialized knowledge, skills and personality traits they need in the field. The interviews conducted with BE teachers reveal that they are likely to be at an advantage if they gain some knowledge of essential business terminology, functions and processes, acquire the essentials of BE teaching methodology, and develop certain skills and personal characteristics which are highly appreciated by the MNC business community. The results imply that compliance with corporate requirements and fulfilment of the immediate needs of BE learners are likely to be the key factors of BE teacher professionalism. Therefore, acquiring BE teacher competencies is vital for the successful delivery of any BE course.